FEATURES OF COMPUTER-TOMOGRAPHIC MEASUREMENTS OF THE THALAMUS AND THE REAR LEGS OF THE INTERNAL CAPSULE IN PRACTICALLY HEALTHY BOYS AND GIRLS OF PODILLYA - Gunas, I.V.; Babych, L.V.; Majewski, O.Je. (World of Medicine and Biology, 2014)
The purpose of this study was to establish the boundaries of percentile range and features computer-tomographic measurements of the thalamus and the rear legs inside the capsule of the brain in healthy urban boys and girls Skirts of different kraniotipes. In practically healthy urban boys and girls of Podolie we limits percentile scale computer-tomographic parameters of the thalamus and the rear legs inside capsules in different kraniotipes. Only between young kids of different kraniotipes identified differences in the magnitude of the computer-tomographic measurements of the thalamus. Installed size dimorphism of the thalamus and the rear legs of the internal capsule, as well as signs of asymmetry of data sizes in different kraniotipes.